A Speech recognition of isolated words in the “Baoulé” language via back-propagation neural networks (BNN) - KOUASSI, Francis Adlès; KONAN, Hyacinthe Kouassi; COULIBALY, Mamadou; ASSEU, olivier (European Journal of Applied Sciences, 2022)
The main objective of this research is to explore how a back propagation neural network (BNN) can be applied to the speech recognition of isolated words. The simulation results show that a BNN offers an efficient approach for small vocabulary systems. The recognition rate reaches 100% for a 5 word system and 94% for a 10 word system. The general techniques developed in this article can be extended to other applications, such as the recognition of sonar targets and the classification of underwater acoustic signals.